Lieutenant of the Russian Imperial Army Anatoly Petrovich Moser (1889–1943): the «little man» and his fate in mirror of military anthropology - D. I. Petin (Омский научный вестник: Серия "Общество. История. Современность")
The study is dedicated to the life of a representative of a family of serving noblemen known in pre-revolutionary Omsk. The purpose of the work is to present the example of this fate as the position of a former career officer in provincial imperial and Soviet society. The relevance of the work is seen in the fact that the life path of A.P. Moser is a small example of the relatively successful integration of a former officer in Soviet society. Studying the life of this person fills the knowledge about the being of «former people» in the RSFSR — USSR. The basis for the preparation of the work was unpublished sources from the funds of the Russian State Military Historical Archive, the Historical Archive of the Omsk Region, as well as an interview with the author’s granddaughter of the article’s hero. The author comes to the conclusion that the anthropological vision of the plots of political and everyday history allows us to draw general conclusions about the state, society, strategies and forms of social survival on the basis of particular cases